Stem Cell Research & Therapy - O'Brien, Timothy; Tuan, Rocky S.
Stem Cell Research & Therapy is the major forum for translational research into stem cell therapies. An international peer-reviewed journal, it publishes high-quality open access research articles with a special emphasis on basic, translational and clinical research into stem cell therapeutics and regenerative therapies, including animal models and clinical trials. The journal also provides reviews, viewpoints, commentaries, reports and methods.